The world may not be just but you'd better not say it: on the social value of expressing personal belief in a just world - Alves, H. V. (2018)
The expression of personal belief in a just world (PBJW) has been discussed as a criterion of excellence in social judgments. In four experimental studies we hypothesized and found that targets who express high versus low PBJW are judged as more: (i) deserving of success and (ii) suited to socio‐organizational expectations. The four studies show that suitability to socio‐organizational expectations mediates the relation between PBJW expressed and success deservingness, even after controlling for judgments of likability, status, rationality, optimism, and targets as victims. Studies 2 and 3 show this pattern occurs regardless of target performance appraisal. Study 4 indicates that expressing low PBJW decreases the social value of individuals, but expressing high PBJW does not increase it. We discuss the impact of PBJW expression on people's lives, namely on upward social mobility of members of low‐status groups, and the influence of the negativity bias on judgments caused by PBJW expression.